BUBBLEBOWL HUS (HOUSE UNDER SEA): PERUMAHAN BAWAH LAUT RAMAH EKOSISTEM DI PANTAI JAKARTA UTARA - Atmaji, Donny Prasetya; Asrim, La Ode Nizam; Pratama, Muhammad Arsyad Putra; Hasanah, Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The high population density and land subsidence is a major problem that threatens the population of northern Jakarta. Land used for new resident housing and green space is very hard to find. Making Bubblebowl aim to formulate the concept of the use of land from the sea with preserve the ecosystems therein, reduce the density of population on land, and realize the land as a city park.so can anticipate and prevent sinking of the northern city of Jakarta. The method used is pay attention to the mechanical effect that occurs and analyze based on calculations and concepts defined.